1989
DOI: 10.1002/chin.198909036
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Properties of Dioxygenyl Tetrafluoroargentate(III).

Abstract: Reaction between O2F2 and Ag compounds, conducted in ClF5, affords the title compound O2+AgF4‐ along with AgF3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 0 publications
0
12
0
6
Order By: Relevance
“…AgF 3 was synthesized by Z Ï emva et al [16] as late as in 1991. It seems that previous claims of AgF 3 by Bougon et al [86] and by Kiselev et al [13] were not sufficiently documented. The structure of AgF 3 was finally refined in the hexagonal system.…”
Section: Compoundmentioning
confidence: 50%
See 4 more Smart Citations
“…AgF 3 was synthesized by Z Ï emva et al [16] as late as in 1991. It seems that previous claims of AgF 3 by Bougon et al [86] and by Kiselev et al [13] were not sufficiently documented. The structure of AgF 3 was finally refined in the hexagonal system.…”
Section: Compoundmentioning
confidence: 50%
“…Then, in 1971 the measurements of Fischer et al [15] confirmed the orthorhombic structure derived previously by Charpin et al, and the structure of a-AgF 2 was refined. Still, in 1988 a new structure (pseudohexagonal with unit cell dimensions of a 5.870, b 5.572, c 5.112 ) was proposed by Kiselev et al [81] for a solid with formal composition AgF 2 . The latest data by Jesih et al [82] agreed again with the assignment made by Charpin et al…”
Section: Compoundmentioning
confidence: 99%
See 3 more Smart Citations